To generate a Pythagorean triple using the given polynomial identity \((x^2 + y^2)^2 = (x^2 - y^2)^2 + (2xy)^2\) with \(x = 10\) and \(y = 6\), we first calculate \(x^2\) and \(y^2\):
\[ x^2 = 10^2 = 100 \] \[ y^2 = 6^2 = 36 \]
Now we can compute each component of the identity.
- Calculate \(x^2 + y^2\):
\[ x^2 + y^2 = 100 + 36 = 136 \]
- Calculate \(x^2 - y^2\):
\[ x^2 - y^2 = 100 - 36 = 64 \]
- Calculate \(2xy\):
\[ 2xy = 2 \cdot 10 \cdot 6 = 120 \]
Now, we can substitute these values into the identity:
\[ (x^2 + y^2)^2 = 136^2 \] \[ (x^2 - y^2)^2 + (2xy)^2 = 64^2 + 120^2 \]
Now we can calculate \(136^2\), \(64^2\), and \(120^2\):
\[ 136^2 = 18496 \] \[ 64^2 = 4096 \] \[ 120^2 = 14400 \]
Now we can verify the identity:
\[ 64^2 + 120^2 = 4096 + 14400 = 18496 \]
The identity holds true.
The Pythagorean triple generated from the values we computed is:
- One of the values is \(120\) (from \(2xy\)).
Thus, the correct answer is \(120\).